STUDY OF BIOFILM FORMATION IN GRAM POSITIVE CLINICAL ISOLATES AND ASSOCIATED RISK FACTORS - MUKESH SWARNAKAR; KARUNA TIWARI; TUHINA BANERJEE (International Journal of Pharma and Bio Sciences, 2013)
Biofilm production in bacteria causing infections is of recent interest especially in relation to emerging drug resistance and increased use of medical devices. The present study was performed to determine biofilm production among pathogenic Gram positive cocci in association with antibiotic resistance and other risk factors. A total of 100 clinical isolates of Staphylococcus aureus (50) and enterococci (50) were included for antibiotic susceptibility testing and semi-quantitative biofilm production assay. Fischer’s exact test was used to study the association of infection with biofilm producers and other risk factors. Biofilm production varied with drug resistance and use of indwelling urinary catheters, intravascular catheters and prolonged hospital stay were significant risk factors (p<0.05). Prudent use of antibiotics and invasive devices should be considered along with a better understanding of the mechanisms of biofilm formation for effective control of these biofilm producing organisms.